SARS-CoV-2 Accessory Protein ORF7b Mediates Tumor Necrosis Factor-α-Induced Apoptosis in Cells - Yang, Ruiping; Zhao, Qiong; Rao, Jingjing; Zeng, Feng; Yuan, Shengren; Ji, Manshan; Sun, Xiaoguang; Li, Jian; Yang, Jing; Cui, Jingwen; Jin, Zhixiong; Liu, Long; et al. (Frontiers in Microbiology, 2021)
The accessory proteins of coronaviruses are essential for virus–host interactions and the modulation of host immune responses. It has been reported that accessory protein ORF3a encoded by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can induce apoptosis, and accessory protein ORF6 and ORF8 could be inhibitors of the type-I interferon (IFN) signaling pathway. However, the function of accessory protein ORF7b is largely unknown. We investigated the apoptosis-inducing activity of ORF7b in cells. Cytokine levels and host innate immune responses, including expression of interferon regulatory transcription factor (IRF)-3, signal transducer and activator of transcription (STAT)-1, interferon (IFN)-β, tumor necrosis factor (TNF)-α, and interleukin (IL)-6, were also investigated. We found that ORF7b promoted expression of IFN-β, TNF-α, and IL-6, activated type-I IFN signaling through IRF3 phosphorylation, and activated TNFα-induced apoptosis in HEK293T cells and Vero E6 cells. These results could provide deeper understanding about the pathogenicity of SARS-CoV-2 as well as the interaction between the accessory protein ORF7b with host immune responses.